Availability of Access, Watch, and Reserve groups of essential antibiotics: a cross-sectional survey - Rafi, Sunaina; Anjum, Syed Muneeb; Usman, Muhammad; Nawaz, Hafiz Awais; Chaudhry, Mamoona; Babar, Zaheer-Ud-Din; Rasheed, Huma (Frontiers in Public Health, 2024)
Background Lower-middle income countries face drastic challenges in Access to essential medicines. Data regarding Pakistan is scarce with no comprehensive study in this regard. The objectives of the study are to document and compare public and private sector availability of all essential antibiotics as well as to conduct a comparison among the AWaRe groups. Methods The study analyzed 103 essential antibiotics comprising 51 Access, 29 Watch, 6 Reserve, and 17 anti-tuberculosis drugs from 15th August to 10th September 2020 in Lahore, Pakistan. It included on-spot physical availability and availability trend surveys. The survey sites included five public tertiary care hospitals with one as anchor and four randomly selected. Their hospital pharmacies and one randomly selected private retail pharmacy from the vicinity each hospital comprised the ten sampling sites. Percentage availability for each antibiotic was categorized as high (>80%), fairly high (50–80%), low (30–<50%), very low (<30–>0%), and not available (0%). Results The mean percentage on-spot availability was 23.76% ± 5.19 (14–25%) for public facilities and 59.20% ± 4.45 (54–66%) for private sector retail pharmacies. The overall percentage of available essential antibiotics varied significantly (p** < 0.001) in public and private sector sampling sites. Except for the Watch group, all other groups showed the mode of 0% availability. A significant difference (p**** < 0.00001) was seen in percentage availability by Access, Watch, Reserve, and anti-TB-all groups of essential antibiotics. The availability trend survey revealed a list of 18 medicines as ‘as never been available’, and five medicines were ‘not available for 5 years or more than 5 years.’ Fourteen medicines as ‘never been heard.’ Conclusion Non-availability of essential medicines is a significant public health challenge at public-sector facilities in Pakistan. It was observed that a number of essential antibiotics were not available in both public and private sectors. A number of corrective strategies are required. This includes the engagement of stakeholder and government bodies. This can help to improve supply chain barriers.